Analysis of trends and status of physician‐based evaluation methods in acne vulgaris from 2000 to 2019. Issue 1 (12th November 2020) - Cho, Soo Ick; Yang, Ji Hoon; Suh, Dae Hun
Abstract: Various evaluation methods for acne severity have been used without standardization, and the diversity of acne outcome measures is an obstacle to the integrated analysis of various acne studies. In this study, we sought to investigate physician‐based evaluation methods used in clinical studies of acne vulgaris and to determine differences according to time, region and study design. PubMed was searched for articles on acne published from January 2000 to June 2019 in five dermatology journals: Journal of the American Academy of Dermatology, JAMA Dermatology, British Journal of Dermatology, Journal of the European Academy of Dermatology and Venereology and Acta Dermato‐Venereologica . A total of 186 articles with acne evaluation methods were selected. Among the selected studies, region, study design, type of intervention and the number of subjects were identified and analyzed. Articles from 2010 to 2019 used Investigator Global Assessment (IGA; odds ratio [OR], 5.808; 95% CI, 1.894–17.811) more often and the Leeds technique (OR, 0.282; 95% CI, 0.098–0.812) less often compared with articles from 2000 to 2009. Controlled experimental studies preferred lesion counting (OR, 238.637; 95% CI, 46.795–1216.954), IGA (OR, 9.177; 95% CI, 3.053–27.586) and Leeds Revised Acne Grading System (LRAGS; OR, 10.844; 95% CI, 3.050–38.559) compared with observational studies. North American studies applied lesion counting (OR, 4.573; 95% CI, 1.173–17.836) and IGA (OR, 11.330; 95% CI, 3.487–36.818) more often and LRAGS (OR, 0.171; 95% CI, 0.039–0.758) less often compared with European studies. This study demonstrated the diversity and heterogeneity of acne outcome measures even in highly influential dermatology journals. This is due to the limitations of current methods and suggests the importance of developing a core outcome measure.